2016
DOI: 10.3758/s13421-016-0606-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of successive relearning on recall: Does relearning override the effects of initial learning criterion?

Abstract: Retrieval practice improves memory for many kinds of materials, and numerous factors moderate the benefits of retrieval practice, including the amount of successful retrieval practice (referred to as the learning criterion). In general, the benefits of retrieval practice are greater with more than with less successful retrieval practice; however, learning items to a higher (vs. lower) criterion requires more time and effort. If students plan on relearning material in a subsequent study session, does the benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 35 publications
1
40
1
Order By: Relevance
“…For instance, in one condition in which relearning sessions were spaced at a 56‐day interval, more than 75% of the items were recalled after a 1‐year delay, and more than 60% of them were still retained after a 5‐year delay (collapsed across the number of relearning sessions). Other investigations of successive relearning have yielded similarly impressive levels of final memory performance (Bahrick, 1979; Bahrick & Hall, 2005; Rawson, Dunlosky, & Sciartelli, 2013; Pyc & Rawson, 2011; Rawson & Dunlosky, 2011, 2013; Rawson et al, 2018; Vaughn, Dunlosky, & Rawson, 2016).…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…For instance, in one condition in which relearning sessions were spaced at a 56‐day interval, more than 75% of the items were recalled after a 1‐year delay, and more than 60% of them were still retained after a 5‐year delay (collapsed across the number of relearning sessions). Other investigations of successive relearning have yielded similarly impressive levels of final memory performance (Bahrick, 1979; Bahrick & Hall, 2005; Rawson, Dunlosky, & Sciartelli, 2013; Pyc & Rawson, 2011; Rawson & Dunlosky, 2011, 2013; Rawson et al, 2018; Vaughn, Dunlosky, & Rawson, 2016).…”
Section: Introductionmentioning
confidence: 81%
“…Alternatively, students may overshoot by overlearning items within a single session (i.e., continuing to practice items after correct recall has been achieved) 1 . In such cases, going to a higher criterion of learning within a single session would likely be inefficient, because the additional correct retrieval attempts typically do not further enhance retention (Rawson et al, 2018; Vaughn et al, 2016). And, as described further below, research on successive relearning in authentic classroom contexts is limited, but the few available laboratory studies on successive relearning demonstrate how powerful and long‐lasting its effects could be for promoting student learning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spacing during the first session had a substantial impact on recall at the start of the second session, but the impact was reduced when the material was restudied and re-learned. Additional studies have confirmed that successive re-learning gradually attenuates effects of initial learning conditions such as spacing and criterion level (Rawson, Vaughn, Walsh, & Dunlosky, in press;Vaughn, Dunlosky, & Rawson, 2016). This has been called the re-learning override effect.…”
Section: Attenuated Spacing Effect With Re-learningmentioning
confidence: 90%
“…Latencies may be particularly informative in the case of a bifurcated distribution, allowing assessment of memory strength for the upper portion of the distribution (i.e., the items that were recalled on the practice test), considering that accuracy is nearly perfect for these items on the final test. Several studies have examined recall latency as a measurement tool to index retrieval effort during test practice (Pyc & Rawson, 2009;Vaughn, Dunlosky, & Rawson, 2016). A few others examined final recall latency following recall practice, finding that participants are faster to recall items after recall practice with free recall (Lehman, Smith, & Karpicke, 2014) and with cued recall (van den Broek, Segers, Takashima, & Verhoeven, 2014; also see Keresztes, Kaiser, Kovács, & Racsmány, 2014;van den Broek, Takashima, Segers, Fernández, & Verhoeven, 2013).…”
Section: Retrieval Practicementioning
confidence: 99%